Pengelolaan mangrove berbasis masyarakat di Pantai Timur Surabaya - Iqbal Ghazali; Isdradjad Setyobudiandi; Rilus A. Kinseng (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2014)
This aims of the study was to descript and evaluate the mangrove management strategy by local community (local wisdom) in East Coast Surabaya.. The survey method was utilized in this study using the stakeholder analysis and AWOT analysis. Primary data were collected through observation on object of study and by in-depth interviews, while secondary data were obtained through the literature review and reports. The results showed there were 50 stakeholders involved in the management of Pamurbaya mangrove, which was divided into three groups i.e. government, private and community. Local wisdom priority was mangrove ecotourism. The strategy for development of mangrove ecotourism was by increasing the institutional capacity and creativity, innovation of eco-tourism workers, and improvement of cooperation with related agencies.